1999
DOI: 10.1097/00000539-199905000-00034
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Subanesthetic Concentrations of Sevoflurane and Nitrous Oxide, Alone and in Combination, on Analgesia, Mood, and Psychomotor Performance in Healthy Volunteers

Abstract: Healthy volunteers inhaled subanesthetic concentrations of sevoflurane and nitrous oxide. Sevoflurane made nitrous oxide less effective as an analgesic, and nitrous oxide made sevoflurane less effective as a sedative. The two drugs may work at cross purposes on different end points of anesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…All previous studies of anaesthetic mixtures appear to have been at macro‐ or micro‐level. Third, in common with Janiszewski et al , they have demonstrated potentiation between the agents on some parameters (EEG burst suppression) while showing antagonism on others (isolectric EEG).…”
Section: The Possibility Of Infra‐additive Effects In Anaesthetic Commentioning
confidence: 53%
See 1 more Smart Citation
“…All previous studies of anaesthetic mixtures appear to have been at macro‐ or micro‐level. Third, in common with Janiszewski et al , they have demonstrated potentiation between the agents on some parameters (EEG burst suppression) while showing antagonism on others (isolectric EEG).…”
Section: The Possibility Of Infra‐additive Effects In Anaesthetic Commentioning
confidence: 53%
“…In humans at macro‐level, N 2 O has been reported to reduce ‐ not increase ‐ self‐reported feelings of sleepiness with low dose sevoflurane; while in turn sevoflurane antagonised the analgesic effects of N 2 O . Interestingly, Janiszewski et al found that the two agents were additive in their depressive effects on psychomotor performance, suggesting that agents can be differently additive, synergistic or infra‐additive on different macro‐endpoints.…”
Section: The Possibility Of Infra‐additive Effects In Anaesthetic Commentioning
confidence: 99%
“…This was explained by the predominantly subcortical antinociceptive action of N 2 O combined with a weak depressant effect on cortical neurons. 13 Subanaesthetic concentrations of sevoflurane decrease the analgesic effect of N 2 O, 15 which is explained by the stimulation by supraspinal GABA A agonists, such as volatile anaesthetics 16 and benzodiazepines. 17 The interplay of mechanisms may explain the differences in the EEG effects that have been observed during different drug concentrations and combinations.…”
Section: Resultsmentioning
confidence: 99%
“…The tests included visual scanning, auditory reaction time, eye-hand coordination, mental flexibility, sustained attention, speed of information processing and memory 12 13 14. …”
Section: Methodsmentioning
confidence: 99%